MAKNA TRADISI MEUGANG DALAM MASYARAKAT ACEH - Sania, Sania; Saputri, Yuni (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2025)
Meugang is a tradition that is preserved by the Acehnese people to this day. Meugang is held to welcome the month of Ramadan, Eid al-Fitr and Eid al-Adha. Meugang is a manifestation of a religious interpretation that is practiced in the form of Acehnese culture. The practice of Meugang, which usually involves slaughtering animals such as cows or goats and distributing meat to relatives and neighbors, is considered a form of sharing blessings and strengthening friendship. In addition, this tradition also serves as a reminder of the importance of togetherness in undergoing the fasting month with full spiritual awareness. This study answers this by analyzing the form of the meugang tradition, through direct observation, because the researcher is an active participant as a native Acehnese and lives in the midst of society. Furthermore, a review of documents related to the meugang tradition was also conducted. The results of the study show that meugang is one of the practices of Islamic values. This is shown by eating meat as a form of happiness for the Acehnese people, as well as holding a feast expecting rewards from the feast or food alms. This tradition has become ingrained in the Acehnese people, so that this tradition seems to be a religious teaching that is highly recommended, operates as part of religion, and seems to be an obligation ordered by religion.Keywords: Tradision; Meugang; Aceh.